Determinan Partisipasi Individu dalam Kegiatan Kemasyarakatan : Studi Menggunakan Data IFLS 2014 - Hanifah, Nisha (Universitas Labuhanbatu, 2023)
An individual's contribution to society plays an important role in the individual's personal development and encourages social development in a wider scope. Efforts to develop the community environment can be carried out through individual participation in the community and community activities. Through participation in community activities, individuals can expand their social relations and contribute to community empowerment and solving problems in the surrounding environment. This research uses the fifth wave of IFLS data surveyed in 2014 to find out what factors influence individual participation in community activities. With a total number of observations of 28,259 samples, the marginal effect estimation results show that individuals who are male, married, have a job, and have a high sense of individual acceptance in their social environment have a significant positive effect on participation in community activities. However, the urban environment has a significant negative effect on individual participation in community activities.